Time-dependent changes in the instantaneous stiffness of reinforced concrete beams. (1st November 2016) - Murray, Angus; Castel, Arnaud; Gilbert, Raymond Ian; Chang, Zhen-Tian
Highlights: A time-dependent analytical model is proposed to estimate instantaneous stiffness. Bond deterioration through cover-controlled cracking modeled by a scalar damage variable. Effect of shrinkage on bond deterioration accounted for by introducing fictitious mechanical loads. For beams considered in this paper, instantaneous stiffness reduced by 25% on average. Good agreement is achieved between predicted and observed instantaneous stiffness. Abstract: The instantaneous stiffness of a reinforced concrete (RC) beam deteriorates with time and this fact may have important consequences for the long-term in-service behavior of RC structures, particularly those that are subjected to repeated loads, vibrations or dynamic effects. There are two main causes of the time-dependent deterioration of instantaneous stiffness. The first is the formation of new primary cracks, both within and outside of the original cracked region of the beam. The second is the propagation of fine cone-shaped cracks that originate at the steel-concrete interface and are mainly confined within the cover concrete. These cover-controlled cracks facilitate a reduction in bond that is manifested in a decay of tension stiffening within the cracked region of the beam. The formation and propagation of both primary cracks and cover-controlled cracks are driven by the combined effects of shrinkage-induced tensile stress in the concrete and a reduction of the concrete's tensile strength under sustained stress (creep rupture). This paper presents an analytical model for the estimation of the instantaneous stiffness of RC beams with a particular focus on time effects. The model is shown to agree well with recent experimental results.